Gender difference in fatigue index and power output / Muhammad Zikry Riduan ... [et al.]. - Riduan, Muhammad Zikry; Abu Kasim, Nurul Ain; Raja Hussain, Raja Nurul Jannat; Mohamed, Muhamad Noor; Mazaulan, Mardiana; Syed Mud Puad, Sharifah Maimunah; Md Radzi, Noor Azila Azreen; Mohd Saleh, Maisarah; Shari, Maisarah (2024)
Understanding how men and women react differently to high-intensity exercise is critical for designing effective training regimens. Research suggests that men can become fatigued even if they generally have a greater peak strength compared to women. This study investigates potential sex-based differences in fatigue resistance and power production. Healthy volunteers of both genders will go through a Running-Based Anaerobic Sprint Test (RAST) methodology. The RAST measures peak power output (PPO), which is the greatest power generated during a sprint, and fatigue index, which is the drop in power output during repeated sprints. Twenty-four (N = 24) participants were divided into two groups, twelve (n =12) male participants and twelve (n = 12) female participants, to perform RAST. The statistical study will compare these measures across genders. This study seeks to determine if men and women differ significantly in fatigue resistance and power generation during high-intensity exercise. The findings can help to build gender-specific training tactics that address each sex’s unique physiological responses. An Independent Sample T-Test was used to analyse the data obtained. The minimum power output recorded for females was (M = 94.3, SD = 35.7), whereas male data reported that the minimum power output was (M = 136.8, SD = 51.1) with p = 0.027. The maximum power was (M = 251.2, SD = 42.8) for female participants and males was (M = 504.2, SD = 345.9), and the p-value reported was 0.020. The findings of the fatigue index results showed that females had (M = 3.30, SD = 0.77) while males showed (M = 8.92, SD = 8.01) with a significant p-value of 0.024. The results indicated there was a significant difference in power output and fatigue index between males and females.